Monogenic auto-inflammatory diseases in children and adults: what a rheumatologist should know - S. O. Salugina; E. S. Fedorov; E. M. Agafonova (Научно-практическая ревматология)
The article presents information on the current state of the problem of autoinflammatory diseases (AID) in rheumatology, reflects the clinical and demographic, laboratory and molecular genetic characteristics of the main monogenic AID (mAID), the most common in real clinical practice. Approaches to the diagnosis and differential diagnosis of these conditions are presented. The variants of classification and diagnostic criteria of the most studied mAID are discussed. The principles of treatment with an emphasis on the use of targeted therapy with interleukin 1 (IL1) inhibitors are shown. The clinical examples demonstrate the variants of late diagnosis of the mAID in adult patients with the disease onset in childhood. Different variants of multi-organ damage are considered. Effectiveness of therapy with IL1β inhibitor kanakinumab is demonstrated. Even in such cases it provided the possibility of significant symptoms regression and restoration of a satisfactory quality of life.